Yipping Tiger And Other Tales from the Neuropsychiatric Clinic - Sachdev, Perminder (University of NSW Press, 2009)
Perminder Sachdev explores the complexity of the human brain through ten fascinating case-studies from the neuropsychiatric clinic. From alien hand syndrome, anorexia nervosa, frontal lobe dysfunction and phantom limb to coprolalia in Tourette's Syndrome, dementia and golfer's cramp, he provides an understanding of how each disorder has been conceptualised and treated and the challenges that it poses for both the neuropshychiatrist and his patient
Description based on publisher supplied metadata and other sources
Keywords: Neurobehavioral disorders -- Case studies; Neurobehavioral disorders -- Patients -- Biography; Neurobehavioral disorders -- Research; Biografie; Fallstudiensammlung